Gastric injury induced by Non-steroidal Anti-inflammatory Drugs and therapeutic strategies for prevention - Pineda-Peña, Elizabeth Arlen; Chávez-Piña, Aracely Evangelina (Mexican Journal of Medical Research ICSA, 2017)
The toxicity of gastrointestinal (GI) tract associated with the use of nonsteroidal anti-inflammatory drugs (NSAIDs) is an important medical and socio-economic problem. The coprescription of traditional gastroprotective drugs such as proton pump inhibitors (PPIs) and H2-receptor antagonist, to reduce gastric acid secretion are the common clinical therapeutically approach. However, these strategies are not effectively to reduce gastrointestinal adverse events of NSAIDs and recently have demonstrated their low safety in long-term use. In the search for new therapeutically approach, the use of selective COX-2 inhibitors and the use of prostaglandin analogue in order to maintain the local prostaglandins was considered. Unfortunately, their adverse events in cardiovascular or renal system provoked that their therapeutic use were discarded. Therefore, the search for new therapeutic strategies has been promoted. The current experimental and preclinical approaches includes very promising alternatives such as H2S-NSAIDs, NO-NSAIDs and the possible use of Docosahexaenoic acid (DHA), an Omega-3 Fatty acid. In this regard, DHA is focused in face the prostaglandin independent mechanism of NSAID-induce gastric injury such as increment of proinflammatory molecules expression and neutrophil–endothelial adherence. However, large studies of these therapeutically approaches are still needed.